Intra-epithelial lymphocytosis of the ileum: A pathological clue to clinically occult adult celiac disease - Freeman, Hugh J; Webber, Doug (International journal of celiac disease, 2017)
A 39-yr-old male presented with diarrhea, weight loss and rectal bleeding. Hemorrhoids were present but the colon and distal ileum were macroscopically normal. Random mucosal biopsies of the ileum and multiple sites in the colon revealed extensive ileal and focal cecal intra-epithelial lymphocytosis. Subsequent duodenal mucosal biopsies confirmed the suspicion of adult celiac disease. Later endoscopic biopies done after gluten-free diet treatment were normal. This report demonstrates that intra-epithelial lymphocytosis in the ileum may be an important pathological clue to underlying clinically occult adult celiac disease.
Keywords: Intraepithelial Lymphocytes; ileitida; celiakie; lidé; Lymphocytosis; mužské pohlaví; Biopsy; Adult; Celiac Disease; Ileum; ileum; Colitis, Lymphocytic; Colon; Enteritis; Humans; kolon; Ileitis; biopsie; intraepiteliální lymfocyty; dospělí; lymfocytóza; kolitida lymfocytární; enteritida; Male